2018
DOI: 10.3390/ijerph15091952
|View full text |Cite
|
Sign up to set email alerts
|

Work Related Stress, Well-Being and Cardiovascular Risk among Flight Logistic Workers: An Observational Study

Abstract: Work-related stress is a known occupational hazard, with a putative role on the development of cardiovascular diseases (CVD). Although several investigations have explored the association in various workplace scenarios, none have focused on the airport flight logistic support personnel, a transportation business of crucial importance, potentially exposed to job stress and consequently to an increase in CVD risk. We explored the relationship between work-related stress and cardiovascular risk in 568 healthy wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…One of the innovative aspects highlighted by the model is the existence of a significant relationship between the CCA and the POS, considering the CCA as an antecedent of the POS. The relevant association between POS and WRS confirmed recent findings on the role of social support in influencing some outcomes of work related stress such as perceived well-being and workplace bullying [69,70].…”
Section: Discussionsupporting
confidence: 86%
“…One of the innovative aspects highlighted by the model is the existence of a significant relationship between the CCA and the POS, considering the CCA as an antecedent of the POS. The relevant association between POS and WRS confirmed recent findings on the role of social support in influencing some outcomes of work related stress such as perceived well-being and workplace bullying [69,70].…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies have shown various complications of stress. For example, stress can contribute to increased risk of cardiovascular diseases [15], while burnout, as an outcome of extended exposure to stress, can be associated with impairment of psychological resources, such as emotional intelligence and self-efficacy, as well as loss of social support [16]. Moreover, it was shown that burnout can negatively affect well-being at work, resources for coping, ability to work, and engagement [17].…”
Section: Introductionmentioning
confidence: 99%
“…Mental health in occupational settings is a major topic for occupational medicine, psychology, and social science [1,2], with important implications for general health, psychological well-being, and company productivity [3,4]. Since the decrease of classic occupational disease, due to the general improvement of working conditions, more attention is being paid to the mental well-being of employees.…”
Section: Introductionmentioning
confidence: 99%